2023
DOI: 10.3389/fonc.2023.1177557
|View full text |Cite
|
Sign up to set email alerts
|

Survival and complications after neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy for locally advanced gastric cancer: a systematic review and meta-analysis

Abstract: BackgroundThere is increasing evidence that neoadjuvant chemoradiotherapy is superior to neoadjuvant chemotherapy for patients with locally advanced gastric cancer. However, a number of studies have come to the opposite conclusion. Therefore, our meta-analysis is to evaluate the efficacy and safety of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy in the treatment of locally advanced gastric cancer.MethodsWe searched Wanfang Database, China National Knowledge Network database, VIP database, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Neoadjuvant therapy can increase the possibility of multimodal combination treatment, especially when serious complications related to surgical treatment arise, which may hinder the timely and effective administration of adjuvant therapy. [ 15 – 16 ] Although there is currently a lack of global consensus on the necessity, timing, and specific regimens of neoadjuvant therapy, from a clinical perspective, it has been observed that neoadjuvant therapy can reduce the incidence of associated complications before performing extensive surgery on patients. It also provides an opportunity to assess the tumor’s biological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant therapy can increase the possibility of multimodal combination treatment, especially when serious complications related to surgical treatment arise, which may hinder the timely and effective administration of adjuvant therapy. [ 15 – 16 ] Although there is currently a lack of global consensus on the necessity, timing, and specific regimens of neoadjuvant therapy, from a clinical perspective, it has been observed that neoadjuvant therapy can reduce the incidence of associated complications before performing extensive surgery on patients. It also provides an opportunity to assess the tumor’s biological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…DFS, disease-free survival. diagnosed with advanced-stage disease [18]. Surgical intervention is considered a curative approach in current clinical practice for patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…GC is one of the most threatening cancers worldwide [17]. Owing to the lack of highly specific and sensitive early diagnostic indicators, most patients with GC are diagnosed with advanced-stage disease [18]. Surgical intervention is considered a curative approach in current clinical practice for patients [19].…”
Section: Discussionmentioning
confidence: 99%